A method for reducing porosity in oil-less bearings using copper-based alloy powder and laser cladding process
Patent Information
- Application Number
- CN202410358874.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-03-27
AI Technical Summary
Existing technologies cannot effectively reduce the porosity of CuSn12Ni2 copper alloy in oilless bearings, which limits the overall mechanical properties and service life of the bearings.
By employing copper-based alloy powder and laser cladding technology, and adjusting the alloy powder composition and process parameters, including the combined use of Sn, Ni, Fe, B, and Ti elements, as well as high power density, appropriate linear velocity, and argon protection, high-quality cladding of copper alloy layers is achieved, with porosity controlled below 0.2%.
The porosity of the CuSn12Ni2 alloy cladding layer was controlled below 0.2%, the shear strength was higher than the industry requirements, the cost of alloy powder was reduced to 95%, the powder preparation process cost was comparable to the existing technology, and the cladding efficiency was improved by 15%.
Smart Images

Figure CN118166348B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a copper-based alloy powder and a laser cladding process, specifically to a method for reducing the porosity of oil-free lubricated bearings using copper-based alloy powder and a laser cladding process. Background Technology
[0002] Motor bearings made with 42CrMo steel as the base material require a CuSn12Ni2 tin bronze alloy layer on their surface to improve lubrication and wear resistance. Existing solutions for adhering the CuSn12Ni2 alloy to the base material surface include inlaying copper-based bushings, arc welding of copper alloy, and centrifugal casting. However, inlaying copper-based bushings has a long processing cycle and poor adhesion between the copper alloy and the base material; arc welding of copper alloy results in excessive dilution of the base material; while centrifugal casting is a commonly used technique in the oil-free lubrication bearing industry. Centrifugal casting uses centrifugal force to rapidly solidify molten copper alloy onto the surface of an iron-based base material, forming a metallurgically bonded coating.
[0003] To control the dilution rate of the base material on the copper alloy, the casting cooling rate used in this industry is often relatively fast. Therefore, during the rapid cooling process of the molten copper alloy, pores and inclusions cannot float to the surface of the cast copper alloy layer, thus affecting the service life of the copper alloy. To solve this problem, some have added trace amounts of phosphorus (P) or P / Zn composites to the CuSn12Ni2 alloy to improve its casting performance. However, the effect is minimal because the content range of the three main elements in CuSn12Ni2—Cu, Sn, and Ni—is strictly limited to ensure the self-lubricating and mechanical properties of the copper alloy. Figure 1 As shown. This will raise another problem: if the amount of P and Zn added is too small, the effect will be minimal. If the amount added is too large, the content range of Cu, Sn, and Ni will not only exceed the standard, but the low vaporization point of P (phosphorus oxide) and Zn elements will also easily cause vapor porosity in the casting layer of copper alloys. On the other hand, due to the country's strong promotion of industrial upgrading and green technology manufacturing, centrifugal casting is energy-intensive and polluting, and the oil-free lubricated bearing industry urgently needs a new technology to replace centrifugal casting.
[0004] Laser cladding technology perfectly meets the current urgent needs of the industry. It can form a metallurgical layer combining dissimilar metals such as copper-based, nickel-based, and cobalt-based metals on iron-based alloy substrates, with negligible dilution and burn-off rates, thus satisfying [the industry's requirements]. Figure 1 The range of ingredients.
[0005] Chinese patent application CN115821251A discloses a blue-red laser composite cladding process for tin bronze alloy powder. The alloy powder is designated CuSn12Ni2, with the following composition: Sn: 11.60%, Ni: 1.97%, P: 0.04%, Fe: 0.07%, Zn: 0.002%, O: 0.016%. The contents of Pb, Si, C, Sb, and Al are all less than 0.01%, with the balance being Cu. The patent mentions that P and Zn elements can improve (casting) fluidity, but does not explain how to use the alloy powder or cladding process to reduce the porosity of the copper-based alloy layer.
[0006] Chinese patent CN112430811B discloses a method for laser cladding copper alloy powder onto a copper substrate. The copper alloy powder used in this patent contains 10-50% Cu and 30-80% Ni, but makes no mention of Sn. Since the copper alloy used in the oil-free lubrication bearing industry is CuSn12Ni2 alloy, which strictly stipulates that the Cu content must not be less than 84.0% and the Ni content must not be more than 2.5%, and Sn is an indispensable element that plays a crucial role in improving the mechanical and lubrication properties of the copper alloy, this patent clearly does not meet the technical requirements of this industry.
[0007] Furthermore, Chinese patent CN114016017B discloses a method for laser cladding copper alloys onto cast iron surfaces and a surface structure for an explosion-proof impeller. The copper alloys disclosed in this patent include CuSn15, CuSn10, CuSn12, CuSn20, and CuSn30, and Inconel 718 is used for the initial cladding to improve the compatibility between the copper alloy and the cast iron substrate. However, the solution provided in this patent does not mention the Ni content or methods for reducing the porosity of the copper alloy.
[0008] In the oil-free lubrication bearing industry, the porosity of CuSn12Ni2 copper alloy directly affects the bearing's overall mechanical properties, service life, and safe service index. The industry generally requires that the pore area of CuSn12Ni2 copper alloy, within the field of view magnified 100 times by an optical microscope, should not exceed 0.2%, i.e., the porosity should be less than or equal to 0.2%. Summary of the Invention
[0009] To address the aforementioned problems, this invention proposes a method for reducing the porosity of oil-free lubricated bearings using copper-based alloy powder and laser cladding technology. The composition of the copper-based alloy powder used in the laser cladding technology is as follows: Sn: ≥11.3wt%; Ni: ≤2.40wt%; Fe: 0.8~1.0wt%; Ti: 0.09~0.12wt%; B: 0.30~0.35wt%; O: ≤0.04wt%; Cu is the balance.
[0010] Furthermore, in the composition of the copper-based alloy powder used in laser cladding technology, Sn is 11.3–11.5 wt% and Ni is 2.30–2.40 wt%.
[0011] Furthermore, in the process parameters used for laser cladding, a fiber laser with a power of 9000-10000W and a power density of 160-312W / mm2 is selected.
[0012] Furthermore, in the process parameters used for laser cladding, a linear velocity of 25–30 mm / s is selected.
[0013] Furthermore, the overlap is 45-50% of the length of the light spot, and the cladding thickness on one side is 1.8-2.2 mm.
[0014] Furthermore, in the process parameters used in the laser cladding process, argon gas protection is set, and the argon gas flow rate for protecting the laser molten pool is 20-25 L / min.
[0015] Furthermore, a continuous spiral overlapping method is used to perform laser cladding on the surface of the oil-free bearing substrate.
[0016] The beneficial effects of this invention are as follows:
[0017] The porosity of the CuSn12Ni2 alloy cladding layer is controlled below 0.2%; while ensuring that the contents of Cu, Sn, and Ni are within the standard range, the total amount of added alloying elements does not exceed 1.5wt%; the shear strength is higher than the industry requirement of 230MPa; the raw material cost of the alloy powder is 95% of that of the standard CuSn12Ni2 alloy; the powder preparation process cost is comparable to existing technologies; and with a cladding thickness of 1.8–2.2 mm, the efficiency of laser cladding is 15% faster than existing technologies. Attached Figure Description
[0018] Figure 1 The standard composition diagram of CuSn12Ni2;
[0019] Figure 2 This is an optical micrograph (OM) of the pore defects in the fusion region between the laser cladding layer and the substrate (100x magnification).
[0020] Figure 3 This is an optical micrograph (OM) of the pore defects in the shallow layer of laser cladding (100x magnification).
[0021] Figure 4 The images show the appearance of the cladding layer when only element B (excluding element Ti) is added, based on the laser cladding process parameters provided in Examples 1 to 3.
[0022] Figure 5 The images show the appearance of the cladding layer when Ti element is added alone (excluding B element) during laser cladding, based on the laser cladding process parameters provided in Examples 1 to 3.
[0023] Figure 6 The image shows the appearance of the cladding layer when B and Ti elements are used together, based on the laser cladding process parameters provided in Examples 1 to 3.
[0024] Figure 7 To illustrate the processing of the alloy powder and laser cladding process parameters provided in Examples 1-3, an optical micrograph (OM) of the cladding layer is shown (100x magnification, with a porosity of 0.15% shown in the figure).
[0025] Figure 8 The images show the appearance of the cladding layer after burn-off when the B element content is less than 0.30 wt% during laser cladding according to the process parameters provided in Examples 1 to 3. Detailed Implementation
[0026] The present invention will be further described below with reference to the accompanying drawings:
[0027] 1. Regarding the selection of alloy components:
[0028] 1.1) Overall Design Concept of Alloy: Observation of the laser cladding layer using an optical microscope (OM) revealed that the porosity defects in the cladding layer are mainly concentrated in two locations: a) the metallurgical transition zone between the cladding layer and the substrate and its vicinity, such as... Figure 2 As shown; b) the shallow surface layer near the laser cladding, such as Figure 3 As shown. Based on this, to achieve a porosity of less than 0.2% in the laser cladding layer of CuSn12Ni2 alloy, the present invention provides a solution using a combined "deoxygenation + transition element" design approach. Deoxygenation involves adding alloying elements with a stronger affinity for oxygen than Cu, Sn, and Ni. Furthermore, the oxides formed by these alloying elements have a lower density than Cu, facilitating the removal of slag from the cladding layer and preventing the formation of oxide porosity defects. Transition elements are alloying elements that are compatible with both the iron-based substrate (42CrMo) and the cladding layer (CuSn12Ni2 alloy), preventing delamination and porosity defects in the metallurgical transition zone between the cladding layer and the substrate due to the significant difference in chemical properties between iron and copper.
[0029] 1.2) Sn and Ni elements: Although the composition range of Sn and Ni elements is within... Figure 1(Source: EN1982:1998) The standard has limitations. However, in the solution provided by this invention, based on the characteristics of laser cladding, the Sn content is limited to the lower limit of the standard range, and the Ni content is limited to the upper limit. The advantages of this design are: to minimize the segregation of Sn in the cladding layer and reduce the probability of forming porosity defects such as shrinkage porosity and gas pores; and Ni is infinitely soluble not only with Cu, but also with Fe (γ-Fe). Using the upper limit of Ni can effectively reduce porosity defects in the cladding layer and the transition zone between the cladding layer and the substrate.
[0030] 1.3) Combined Use of Ni and Fe Elements: According to the first principles of materials design, the closer the alloying elements are in the periodic table, the more similar their physical and chemical properties, the greater their solid solubility, the smaller the crystal defects after mutual solubility, and the lower the probability of porosity defects formed by cladding. This is the principle of "like dissolves like" in materials science. The main element in the cladding layer is Cu, accounting for over 84.0 wt%, while the iron content in the base material 42CrMo is over 96 wt%. Cu is element number 29 in the periodic table, Ni is 28, and Fe is 26. Ni's solid solubility with Cu is significantly higher than Fe's. However, Fe's mutual solubility with the base material 42CrMo is significantly higher than Ni's. Fe and Ni belong to the same period and principal axis, meaning they can also be infinitely soluble. Therefore, the combination of Fe and Ni forms a bridge connecting the cladding layer and the base material, reducing porosity defects caused by the significant difference in chemical properties between Fe and Cu. The amount of Fe added depends on the Ni content. When the Ni content is in the range of 2.30–2.40 wt%, and the Fe content is higher than 1.0 wt%, the iron precipitated in the cladding layer will combine with oxygen to form iron oxides, leading to an increase in porosity defects in the cladding layer and making it prone to cracking. When the Fe content is lower than 0.8 wt%, the delamination between the cladding layer and the substrate is obvious, meaning that porosity defects increase in the transition zone between the cladding layer and the substrate.
[0031] 1.4) Combined use of B and Ti: Oxygen is a key element causing porosity defects in the cladding layer. Both B and Ti are strong oxygen-removing elements; however, porosity defects in the cladding layer can only be controlled when they are used together. Under certain conditions of cladding equipment and cladding process, the cladding layer with B added alone... Figure 4 As shown, laser cladding involves significant spatter, and there are numerous unmelted copper alloy particles at the cladding layer boundaries. During overlapping cladding, these unmelted copper alloy particles can easily cause porosity defects. A cladding layer with only Ti element added is shown below. Figure 5 As shown, the cladding layer exhibits obvious wavy lines and pits after laser cladding. This is due to the molten metal not spreading out properly during laser cladding, which directly restricts venting and slag removal, easily leading to porosity and inclusions in the cladding. When B is used in conjunction with Ti, the appearance of the cladding layer is as follows: Figure 6As shown, the surface of the cladding layer is smooth, free of cladding ripples, spatter, and unmelted copper alloy particles. Under an optical microscope, the porosity of the cladding layer can be controlled below 0.18%. Figure 7 As shown. The amount of Ti added is determined based on the unavoidable oxygen content during the powdering process (O ≤ 0.04 wt%). When Ti is greater than 0.12 wt%, the reactive Ti easily causes inclusions in the cladding. When Ti is less than 0.09 wt%, the cladding spatter is large and deoxygenation is insufficient. The amount of B added is determined based on the content of O and Ti mixed into the molten pool during cladding. When B is higher than 0.35 wt%, the cladding spatter is large, and there are many unmelted copper alloy particles at the boundary of the cladding layer. When B is lower than 0.30 wt%, the cladding layer is severely burned and not well-formed, such as... Figure 8 As shown.
[0032] 2. Setting of cladding process
[0033] 2.1) The core of laser cladding technology is power density, that is, the energy density over the laser spot area. Copper has a low absorption rate of laser (below 30%), and the oilless bearing industry requires a relatively thick cladding thickness (1.8-2.2 mm). Under these conditions, a high power density (160-312 W / mm²) is necessary to ensure that the copper alloy powder provided by this invention is completely melted through, thus avoiding porosity defects caused by the cladding process.
[0034] 2.2) When the power density is constant, the range of linear velocity can be determined. When the linear velocity is higher than 30 mm / s, there are more cladding pores. When the linear velocity is lower than 25 mm / s, a large amount of Fe element in the substrate is incorporated into the copper alloy cladding layer, causing cladding porosity defects.
[0035] 2.3) The overlap rate depends on the cladding efficiency and the depth of the overlap groove. While ensuring that the machining allowance is small enough, the cladding efficiency should be as fast as possible.
[0036] 2.4) Argon protection is to prevent oxygen and hydrogen from the air from mixing into the cladding layer and causing porosity defects. When the argon flow rate is higher than 25 L / min, the alloy powder is blown away. When the argon content is lower than 20 L / min, the cladding layer turns black and the burn-off is aggravated.
[0037] Example 1:
[0038] A method for reducing the porosity of oilless lubricated bearings using copper-based alloy powder and laser cladding process. The composition of the copper-based alloy powder used in the laser cladding technology is as follows: Sn: 11.3wt%; Ni: 2.30wt%; Fe: 0.8wt%; Ti: 0.09wt%; B: 0.30wt%; O: 0.01wt%; Cu is the balance.
[0039] The process parameters used in laser cladding are as follows: a 9000W fiber laser is selected, with a power density of 160W / mm², a linear velocity of 25mm / s, an overlap of 45% along the length of the laser spot, a single-sided cladding thickness of 1.8mm, and an argon gas flow rate of 20L / min to protect the laser molten pool. Laser cladding is performed on the surface of an oil-free lubricated bearing substrate using a continuous spiral overlap method.
[0040] After the cladding is completed, the workpiece is placed on a wire cutting machine for sampling and processing. The workpiece is processed according to two standards: YS / T485-2005 "Determination of Shear Strength of Sintered Bimetallic Materials" and GB / T3489-2015 "Metallographic Determination of Porosity and Non-combined Carbon in Hard Alloy". The shear strength and porosity of the cladding layer are tested respectively, and the results are shown in Table 1.
[0041] Table 1: Shear strength and porosity of the cladding layer tested according to the solution provided in Example 1
[0042]
[0043]
[0044] Example 2:
[0045] A method for reducing the porosity of oilless lubricated bearings using copper-based alloy powder and laser cladding process. The composition of the copper-based alloy powder used in the laser cladding technology is as follows: Sn: 11.4 wt%; Ni: 2.35 wt%; Fe: 0.9 wt%; Ti: 0.10 wt%; B: 0.32 wt%; O: 0.02 wt%; Cu is the balance.
[0046] The process parameters used in laser cladding are as follows: a 9500W fiber laser is selected, with a power density of 236W / mm², a linear velocity of 27mm / s, an overlap of 47% along the length of the laser spot, a cladding thickness of 2.0mm on one side, and an argon gas flow rate of 22L / min to protect the laser molten pool. Laser cladding is performed on the surface of an oil-free lubricated bearing substrate using a continuous spiral overlap method.
[0047] After the cladding is completed, the workpiece is placed on a wire cutting machine for sampling and processing. The workpiece is processed according to two standards: YS / T485-2005 "Determination of Shear Strength of Sintered Bimetallic Materials" and GB / T3489-2015 "Metallographic Determination of Porosity and Non-combined Carbon in Hard Alloy". The shear strength and porosity of the cladding layer are tested respectively, and the results are shown in Table 2.
[0048] Table 2: Shear strength and porosity of the cladding layer tested according to the solution provided in Example 2
[0049]
[0050] Example 3
[0051] A method for reducing the porosity of oilless lubricated bearings using copper-based alloy powder and laser cladding process. The composition of the copper-based alloy powder used in the laser cladding technology is as follows: Sn: 11.5wt%; Ni: 2.40wt%; Fe: 1.0wt%; Ti: 0.12wt%; B: 0.35wt%; O: 0.04wt%; Cu is the balance.
[0052] The process parameters used in laser cladding are as follows: a 10000W fiber laser is selected, with a power density of 312W / mm², a linear velocity of 30mm / s, an overlap of 50% along the length of the laser spot, a cladding thickness of 2.2mm on one side, and an argon gas flow rate of 25L / min to protect the laser molten pool. Laser cladding is performed on the surface of an oil-free lubricated bearing substrate using a continuous spiral overlap method.
[0053] After the cladding is completed, the workpiece is placed on a wire cutting machine for sampling and processing. The workpiece is processed according to two standards: YS / T485-2005 "Determination of Shear Strength of Sintered Bimetallic Materials" and GB / T3489-2015 "Metallographic Determination of Porosity and Non-combined Carbon of Hard Alloy". The shear strength and porosity of the cladding layer are tested respectively, and the results are shown in Table 3.
[0054] Table 3: Shear strength and porosity of the cladding layer tested according to the solution provided in Example 3
[0055]
[0056] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A method for reducing the porosity of oilless lubricated bearings using copper-based alloy powder and laser cladding process, characterized in that: The composition of the copper-based alloy powder used in laser cladding technology is as follows: Sn: ≥11.3wt%; Ni: ≤2.40wt%; Fe: 0.8~1.0wt%. Ti: 0.09~0.12wt%; B: 0.30~0.35wt%; O: ≤0.04wt%; Cu is the balance; In the composition of the copper-based alloy powder used in laser cladding technology, Sn is 11.3~11.5wt% and Ni is 2.30~2.40wt%.
2. The method for reducing the porosity of oil-free lubricated bearings using copper-based alloy powder and laser cladding process according to claim 1, characterized in that: The process parameters used in laser cladding include a fiber laser with a power of 9000~10000w and a power density of 160~312w / mm2.
3. The method for reducing the porosity of oilless lubricated bearings using copper-based alloy powder and laser cladding process according to claim 2, characterized in that: The process parameters used in laser cladding are selected with a linear velocity of 25~30mm / s.
4. The method for reducing the porosity of oilless lubricated bearings using copper-based alloy powder and laser cladding process according to claim 3, characterized in that: The overlap is 45-50% of the length of the light spot, and the cladding thickness on one side is 1.8-2.2mm.
5. The method for reducing the porosity of oilless lubricated bearings using copper-based alloy powder and laser cladding process according to claim 4, characterized in that: In the process parameters used for laser cladding, argon gas protection is set, and the argon gas flow rate to protect the laser molten pool is 20~25L / min.
6. The method for reducing the porosity of oil-free lubricated bearings using copper-based alloy powder and laser cladding process according to claim 1, characterized in that: Laser cladding is performed on the substrate surface of oil-free bearings using a continuous spiral overlapping method.
Citation Information
Patent Citations
A method for laser cladding copper alloy powder on a copper substrate
CN112430811B
A method for laser cladding copper alloy onto cast iron surface and an explosion-proof impeller surface structure
CN114016017B
Process for cladding tin bronze alloy powder by blue and red laser compounding
CN115821251A
Laser cladding technological method and alloy material for laser cladding
CN102168210A
Laser cladding composite material, laser cladding equipment and preparation method of laser cladding composite material
CN115747792A
